ผลกระทบจากการส่งเสริมสถานที่ท่องเที่ยวรูปแบบ Theme Park ที่ส่งผลต่อการกระจายรายได้ต่อชุมชนในท้องถิ่นอำเภอชะอำจังหวัดเพชรบุรี กรณีศึกษา: ซานโตรินี่พาร์ค - อินทรกำจร ธมลวรรณ (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2015)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลกระทบทางด้านเศรษฐกิจจากการพัฒนาการท่องเที่ยวรูปแบบ Theme Park ซานโตรินี่ที่มีต่อการกระจายรายได้ต่อชุมชนในท้องถิ่นอำเภอชะอำ จังหวัดเพชรบุรี และเปรียบเทียบผลกระทบจากการส่งเสริมสถานที่ท่องเที่ยวรูปแบบ Theme Park (ซานโตรินี่) ที่ส่งผลต่อการกระจายรายได้สู่ภาคครัวเรือนในท้องถิ่นของชาวบ้านอำเภอชะอำ จังหวัดเพชรบุรี จำแนกตามปัจจัยส่วนบุคคล กลุ่มตัวอย่างที่ใช้ในการศึกษาคือ ชาวบ้านอำเภอชะอำ จังหวัดเพชรบุรี จำนวน 400 คน โดยใช้แบบสอบถามเป็นเครื่องมือในการเก็บรวบรวมข้อมูล และวิเคราะห์ข้อมูลด้วยโปรแกรมทางสถิติ ผลการศึกษาพบว่า กลุ่มตัวอย่างส่วนใหญ่เป็นเพศหญิง (ร้อยละ 57.3) มีอายุ 31 - 40 ปี (ร้อยละ 36.5) มีการศึกษาระดับปริญญาตรี (ร้อยละ 48.0.5) มีสถานภาพโสด (ร้อยละ 64.0)มีอาชีพเป็นพนักงานองค์กรเอกชน/ลูกจ้าง (ร้อยละ 24.8) และมีรายได้เฉลี่ยต่อเดือน 15,001 – 20,000 บาท (ร้อยละ 22.5) และการส่งเสริมสถานที่ท่องเที่ยวรูปแบบ Theme Park (ซานโตรินี่)ส่งผลต่อการกระจายรายได้ต่อชุมชนในท้องถิ่นอำเภอชะอำ จังหวัดเพชรบุรีในภาพรวมอยู่ในระดับมากเมื่อพิจารณาเป็นรายด้านพบว่า ทุกด้านมีความคิดเห็นอยู่ในระดับมาก โดยด้านที่มีค่าเฉลี่ยมากที่สุดคือด้านการครอบคลุมของการกระจายรายได้ รองลงมาคือด้านระบบเศรษฐกิจ ด้านการกระจายรายได้และด้านโอกาสในการทำงาน ตามลำดับ ผลการทดสอบสมมติฐานพบว่า ชาวบ้านในท้องถิ่นที่อาศัยอยู่ในอำเภอชะอำ จังหวัดเพชรบุรีที่มีปัจจัยส่วนบุคคลคือเพศ อายุ สถานภาพ ระดับการศึกษา อาชีพและรายได้ต่างกันมีผลกระทบจากการส่งเสริมสถานที่ท่องเที่ยวรูปแบบ Theme Park (ซานโตรินี่)ไม่แตกต่างกัน Abstract The purpose of this research is to study the economic impact from tourist development in type of Theme Park, Santorini, toward income distribution to local community in Cha-Am District, Petchaburi Province, and compare the impact from tourist attraction promotion in type of Theme Park (Santorini) toward income distribution to local household sector in Cha-Am District, Petchaburi Province that is categorized according to personal factor. The sample groups used for study are 400 villagers of Cha-Am District, Petchaburi Province. The questionnaire is used as instrument for data collection with data analysis performed by statistical program. According to finding of study most of the sample groups are 57.3% of females, and 42.8% of males, 36% with 31-40 years of age, 48.05% having bachelor’s degree education, 64.0% with single status, 24.8% of occupation being private organization staffs/employees, and 22.5% gaining 15,001 - 20,000 baht monthly income average. The tourist attraction promotion in type of Theme Park (Santorini Park) has affected income distribution to local community in Cha-Am District, Petchaburi Province at high level in overall aspects. When considering individual aspect, it found that there has been high level of opinion for all aspects with maximum average in income distribution coverage, and inferior averages in economic system, income distribution, and working opportunity, respectively. The finding of hypothesis testing result was that the local villagers resided in Cha-Am District, Petchaburi Province, with different personal factors including gender, age, status, educational level, occupation, and income, have been indifferently affected from tourist attraction promotion in type of Theme Park (Santorini Park)